2019
DOI: 10.1111/psyp.13423
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear relations between post‐traumatic stress symptoms and electrocortical reactivity during emotional face processing in combat‐exposed veterans

Abstract: Combat‐related post‐traumatic stress symptoms (PTSS) are prevalent among recently deployed veterans, making identification of biomarkers of PTSS in this population a public health priority. Given the link between threat processing neurobiology and PTSS, the threat‐related late positive potential (LPP), an ERP reflective of attentional processing sensitive to emotion and its regulation, may have utility as a cost‐effective biomarker. Existing PTSS/threat‐related LPP findings are mixed, possibly due to variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In many areas of neuroscience research, including ERP studies, a common approach for calculating difference scores is to subtract activity during one condition ( X , the subtrahend) from activity during another condition ( Y , the minuend; Y − X ). Another approach increasing in popularity is a residualized difference score (e.g., Crane et al., 2021; Hanna et al., 2020; Klawohn et al., 2020; Macatee et al., 2020; Meyer et al., 2017; Muir et al., 2020; Sandre et al., 2020; Schroder et al., 2020; Suor et al, in press). A residualized difference score is the difference between the actual score ( Y ) and predicted score (trueŶ) using a linear regression equation (YŶ), wherein Y scores are regressed on X .…”
Section: Introductionmentioning
confidence: 99%
“…In many areas of neuroscience research, including ERP studies, a common approach for calculating difference scores is to subtract activity during one condition ( X , the subtrahend) from activity during another condition ( Y , the minuend; Y − X ). Another approach increasing in popularity is a residualized difference score (e.g., Crane et al., 2021; Hanna et al., 2020; Klawohn et al., 2020; Macatee et al., 2020; Meyer et al., 2017; Muir et al., 2020; Sandre et al., 2020; Schroder et al., 2020; Suor et al, in press). A residualized difference score is the difference between the actual score ( Y ) and predicted score (trueŶ) using a linear regression equation (YŶ), wherein Y scores are regressed on X .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using EEG, one study found that late positive potential (LPP), an event-related potential that reflects facilitated attention toward emotional stimuli, was related to PTSS with regard to viewing angry faces specifically (DiGangi et al, 2017), suggesting that individuals with PTSD actively avoid looking at angry faces. These results were replicated and clarified by another study, which showed that the more severe PTSS, the greater the LPP effect (Macatee et al, 2020). In a recent study examining childhood maltreatment and PTSD and interpretations of neutral facial expressions, participants with PTSD did not perform any differently than control groups, but higher levels of childhood emotional and sexual abuse, as well as physical neglect, were linked to a more negative interpretation of neutral facial expressions (Pflatz et al, 2019).…”
Section: Ptsd and Angry Face Processingmentioning
confidence: 87%
“…Other studies have contradictorily observed blunted LPP amplitudes to threatening stimuli, relative to nonthreatening stimuli, in adults with combat exposure (Digangi et al., 2017; MacNamara et al., 2013 ). Still others find a quadratic pattern, where those with the lowest and highest PTSD symptoms exhibit larger LPPs to angry faces, but those with more moderate symptom levels showed blunting (Macatee et al., 2020).…”
Section: Introductionmentioning
confidence: 99%